Reviews of Physiology, Biochemistry and Pharmacology
DOI: 10.1007/s10254-003-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Organic cation transporters

Abstract: Over the last 15 years, a number of transporters that translocate organic cations were characterized functionally and also identified on the molecular level. Organic cations include endogenous compounds such as monoamine neurotransmitters, choline, and coenzymes, but also numerous drugs and xenobiotics. Some of the cloned organic cation transporters accept one main substrate or structurally similar compounds (oligospecific transporters), while others translocate a variety of structurally diverse organic cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
291
1

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(300 citation statements)
references
References 289 publications
(377 reference statements)
8
291
1
Order By: Relevance
“…OCT-1 belongs to the solute carrier superfamily and is responsible for the distribution and elimination of organic cations in vivo. 16,17 Using our established intracellular uptake and retention (IUR) assay, 14 we have shown that the functional activity of OCT-1 (OCT-1 Activity) in mononuclear cells (MNC) derived from CML patients is significantly related to their molecular response to imatinib treatment. 18 In addition, other studies have observed a relationship between OCT-1 mRNA levels and achievement of cytogenetic responses to imatinib.…”
Section: Introductionmentioning
confidence: 99%
“…OCT-1 belongs to the solute carrier superfamily and is responsible for the distribution and elimination of organic cations in vivo. 16,17 Using our established intracellular uptake and retention (IUR) assay, 14 we have shown that the functional activity of OCT-1 (OCT-1 Activity) in mononuclear cells (MNC) derived from CML patients is significantly related to their molecular response to imatinib treatment. 18 In addition, other studies have observed a relationship between OCT-1 mRNA levels and achievement of cytogenetic responses to imatinib.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, Caco-2 cells were cultured as described above at 37 °C. After 36 hours, to allow proper attachment, cells were exposed to either 100 µM amantadine (hOCT1&2), 100 µM cimetidine (hOCT1&2&3) [37], 100 µM desipramine (hOCT1&2&3), 10 µM β-estradiol (hOCT1&3) or 10 µM verapamil (hOCT1&P-gp) [28,35,36] for 15 min. Then attached cells were exposed to 10 µM erlotinib, gefitinib, sorafenib, sunitinib, crizotinib or 1 µM dasatinib for 2 hours at 37 °C.…”
Section: Effect Of Specific Oct Inhibitorsmentioning
confidence: 99%
“…Table I), and the identification and characterization of interactions with the hOCT have been primarily accomplished using competitive binding, cellular uptake and trans -stimulation studies (cf. Zhang et al 1998; Koepsell et al 2003; Moaddel et al 2005a). …”
Section: Determination Of Stereoselective Ligand Interactions With Drmentioning
confidence: 99%
“…This family has been recently reviewed (Koepsell et al 2003) and is addressed in this special issue. These transporters interact with a broad range of substrates and inhibitors and, as in the case of Pgp, stereoselective interactions have been reported.…”
Section: Introductionmentioning
confidence: 99%